The teacher-student relationship in inclusive contexts: the role of mentalization and closeness - Cecere, Gelsomina; La Penna, Ilaria; Cerciello, Francesco; Cavallaro, Antonella; Ponticorvo, Michela; Sica, Luigia Simona; Frolli, Alessandro (Frontiers in Psychology, 2025)
The teacher-student relationship is a central element in the educational context and significantly influences students’ academic performance and socio-emotional well-being, with particular attention to teachers working with students with Special Educational Needs (SEN). Scientific literature has recognized several factors that determine the quality of this relationship, such as teachers’ mentalization abilities, their emotion regulation skills, and relational closeness. This study analyzed gender differences in the mentalization abilities of special education teachers and identified the main predictors of relational closeness in educational relationships. The results revealed that female teachers show greater interest in the mental and emotional states of students and tend to be less prone to misinterpretations of them. Moreover, mentalization competencies, particularly interest in and certainty about students’ mental and emotional states, positively predict relational closeness, while difficulties in emotional regulation and a tendency to misinterpret students’ mental and emotional states reduce such closeness. Future research should further explore the relational dynamics between special education teachers and students with Special Educational Needs, utilizing complementary tools for a more comprehensive and accurate assessment.